PENDIDIKAN PRENATAL: TELAAH PEMIKIRAN IBN QAYYIM AL-JAUZIYYAH DALAM KITAB TUHFAH AL- MAUDUD BI AHKAM AL-MAULUD DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Muhammad Abdullah (Universitas Yudharta Pasuruan, 2017)
Human education is a system and a way to improve the quality of life in all fields so that in the history of human life on this earth almost no groups of people who do not use education as a means of culture and quality improvement. The first education starts from the family environment, because of them later generation quality will change the face of the world. In this case Islam is very concerned about how the first education in the family for children (prenatal education) and provide guidance to parents, especially for pregnant mothers to pay attention to the education for children they contain. Ibn Qayyim al-Jawziyyah gave great attention to the concept and input to parents in prenatal education. Because the first education for children is very important that will determine the quality of children after birth. So this study focuses on the concept of Ibn Qayyim Al-Jawziyyah in his work entitled Tuhfah al-Maudud bi Ahkam al-Maulud on prenatal education and how relevant it is to current Islamic education.